2005
DOI: 10.1016/j.physbeh.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of sucrose craving: effects of reduced training and sucrose pre-loading

Abstract: Time-dependent increases in cue-induced reward seeking after forced abstinence were described in rats with a history of cocaine or sucrose self-administration, suggesting reward craving incubates over time. In the present study, we examined the effects of reduced training experience, or sucrose pre-loading just prior to testing, on the incubation of sucrose craving. Sucrose seeking (responding in extinction and then for a sucrose-paired cue) increased over time in groups of rats that selfadministered sucrose 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
111
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 24 publications
14
111
2
1
Order By: Relevance
“…Consistent with previous studies on incubation of nondrug sucrose craving (Grimm et al, 2005;Li and Frantz, 2010;Uejima et al, 2007), we observed incubation of palatable food craving after withdrawal using betweensubject assessment. An unexpected finding was a lack of incubation of food craving using the within-subject assessment.…”
Section: Incubation Of Methamphetamine and Food Craving In Unpunishedsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies on incubation of nondrug sucrose craving (Grimm et al, 2005;Li and Frantz, 2010;Uejima et al, 2007), we observed incubation of palatable food craving after withdrawal using betweensubject assessment. An unexpected finding was a lack of incubation of food craving using the within-subject assessment.…”
Section: Incubation Of Methamphetamine and Food Craving In Unpunishedsupporting
confidence: 91%
“…For comparison purposes, we also assessed incubation of methamphetamine craving under forced abstinence conditions like those typically used in incubation of drug craving studies (Lu et al, 2004b;Pickens et al, 2011). In addition, as incubation of craving has been demonstrated in rats trained to self-administer non-drug rewards (eg, sucrose) (Grimm et al, 2005;Grimm et al, 2002;Lu et al, 2004b), we also tested incubation of reward craving after both forced abstinence and punishment-induced suppression of extended-access palatable food self-administration.…”
Section: Introductionmentioning
confidence: 99%
“…Cue-induced relapse to reward seeking is one model that has provided insight into the neurobiology of drug seeking (Shalev et al 2002) and most recently insight into food seeking (Grimm et al 2005(Grimm et al , 2006Bossert et al 2005). In this animal model, rats respond for the presentation of a stimulus (tone+light) that was previously associated with self-administration of a reward.…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, we and others have identified and characterized a time-dependent increase in responding for drug and food cues during abstinence from selfadministration Bossert et al 2005 for reviews). In addition to the finding that the "incubation" of craving for sucrose is resistant to manipulations designed to reduce it (e.g., satiation with sucrose; Grimm et al 2005), we have found that rats are less sensitive to the response-potentiating effects of cocaine at 1 month of forced abstinence vs 1 day (Grimm et al 2006). This finding suggests time-dependent changes in the sensitivity of brain reward systems and has led us to consider how such transmitter systems might be affected by, or contribute to, the incubation of sucrose craving.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the acquisition of responding for cocaine-and sucrose-paired conditioned reinforcers is topographically similar, and both are equally persistent (Grimm et al 2001(Grimm et al , 2005Di Ciano and Everitt 2004). Therefore, we have employed an acquisition of a new instrumental response with conditioned reinforcement (ANR) procedure to investigate further the pharmacological mechanisms of appetitive memory reconsolidation, using the ␤-adrenergic receptor antagonist propranolol as a putative amnestic agent, with both natural (sucrose) and drug (cocaine) reinforcers.…”
mentioning
confidence: 99%